Variable Resistor - Science History Institute (2016)
Variable resistors are also known as potentiometers. Potentiometers are used to measure electromotive force (emf) by balancing it with a known emf. The concept was first developed in 1841 by J. C. Poggendorff and improved throughout the 19th century by Latimer Clark and J. A. Fleming.
Keywords: Variable Resistor; Potentiometer; Leeds and Northrup Company